2014
DOI: 10.1371/journal.pone.0096595
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Modulation of Human Dendritic Cell Cytokine Secretion: An In Vitro Study

Abstract: Probiotics are live microorganisms which when administered in adequate amounts confer a health benefit on the host. The concept of individual microorganisms influencing the makeup of T cell subsets via interactions with intestinal dendritic cells (DCs) appears to constitute the foundation for immunoregulatory effects of probiotics, and several studies have reported probiotic strains resulting in reduction of intestinal inflammation through modulation of DC function. Consequent to a focus on Saccharomyces boula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 58 publications
3
26
1
1
Order By: Relevance
“…Similarly, K . marxianus induced statistically significant DC secretion of all four cytokines, confirming previous results[10]. While the levels of DC IL-12 and IL-1β secretion appeared to be significantly stronger in response to stimulation with K .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, K . marxianus induced statistically significant DC secretion of all four cytokines, confirming previous results[10]. While the levels of DC IL-12 and IL-1β secretion appeared to be significantly stronger in response to stimulation with K .…”
Section: Resultssupporting
confidence: 90%
“…Further, K . marxianus has been found to engage human immune cells in vitro [9, 10] and is of interest as a potential candidate for development of novel yeast probiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Some probiotics have also been reported to induce the expression of APC activation markers while simultaneously limiting cell activation in response to inflammatory stimuli. For example, while one study reported strong CD80, CD86, and CCR7 upregulation in human APCs exposed to S. boulardii (309), previous studies found that S. boulardii inhibited the lipopolysaccharide-induced upregulation of CD40, CD80, and CCR7 expression in human myeloid cells in vitro (310). It will be important to assess specific inhibitory properties of individual probiotic organisms on mucosal APCs, which are known to have vastly different phenotypic profiles than in vitro bone marrow-or monocytederived phagocytic cells, in order to more accurately assess whether these probiotics may have beneficial effects in the context of UC.…”
Section: Protective Mechanisms Of Probiotics Against Ulcerative Colitismentioning
confidence: 99%
“…and bacterial toxins (C. difficile, V. cholera, and E. coli) (Brandão et al 1998;Gedek 1999;Czerucka et al 2007;Mumy et al 2008;Martins et al 2010;Tiago et al 2012;Martins et al 2013). S. boulardii also affect immune factors, inducing the secretion of sIgA, tumor necrosis factor-alpha (TNF-α), interleukin (IL)-1β, IL-5, IL-6, IL-10, and IL-12, as demonstrated both in vitro and in the colon of murine models (Rodrigues et al 2000;Czerucka et al 2007;Foligné et al 2010;Kourelis et al 2010;Smith et al 2014), while downregulating IL-8 expression by acting in the NF-κB pathway in uninfected enterocytes (Sougioultzis et al 2006;Martins et al 2010) and also in MAPK and AP-1 pathways in Salmonella enterica serovar Typhimurium-infected enterocytes Martins et al 2013). S. boulardii also reduces the levels of pro-inflammatory cytokines IL-6 and TNF-α in models of colitis and infection with pathogenic E. coli (Dalmasso et al 2006;Foligné et al 2010;Plaza-Diaz et al 2014).…”
Section: Mechanisms Of Action Of Probiotic S Cerevisiae Strainsmentioning
confidence: 99%
“…For instance, probiotic strains could be engineered to express antigens for specific intestinal disorders, such as mucin MUC-1 for colon cancer (Byrd and Bresalier 2004) or adhesion protein intimin for pathogenic E. coli O157:H7 (Gedek 1999;Oliveira et al 2012). S. cerevisiae strains with proven probiotic potential could be used as delivery agents of desired biomolecules: they can better withstand the host temperature of 37°C and stresses found in the GIT (Fietto et al 2004;Martins et al 2005;Van der Aa Kühle et al 2005;Diosma et al 2014;Perricone et al 2014) and present immunomodulatory properties (Martins et al 2007;Czerucka et al 2007;Foligné et al 2010;Generoso et al 2010;Romanin et al 2010;Kourelis et al 2010;Martins et al 2011;Zanello et al 2013;Martins et al 2013;Smith et al 2014;Plaza-Diaz et al 2014). Interestingly, some of the probiotic S. cerevisiae strains elicit different immune responses (Kourelis et al 2010).…”
Section: Future Directionsmentioning
confidence: 99%